Simon's minimax and optimal and Jung's admissible two-stage designs with or without curtailment - Kunz, Cornelia Ursula; Kieser, Meinhard (The Stata journal, 2011)
This article describes a new Stata command called simontwostage, which calculates the critical values and sample sizes for two-stage designs for phase II oncology trials. Options are provided to determine the minimax and optimal designs proposed by Simon (1989, Controlled Clinical Trials 10: 1-10) and admissible designs described by Jung et al. (2004, Statistics in Medicine 23: 561-569). Furthermore, nonstochastic and stochastic curtailment rules can be implemented in both stages of the trial, and the properties of the curtailed designs can be examined.
Gesehen am 11.07.2022